RUNX1 (RUNX family transcription factor 1), a target of microRNA miR-128-3p, promotes temozolomide resistance in glioblastoma multiform by upregulating multidrug resistance-associated protein 1 (MRP1). Issue 2 (20th December 2021) - Xu, Jianglong; Song, Jia; Xiao, Menglin; Wang, Changsheng; Zhang, Qisong; Yuan, Xiaoye; Tian, Shaohui
ABSTRACT: Glioblastoma multiform (GBM) is the most frequent type of malignant brain tumor with a poor prognosis. After optimal surgery, radiotherapy plus temozolomide (TMZ) is the standard treatment for GBM patients. However, the development of TMZ resistance limits its efficacy in GBM management. Runt Related Transcription Factor 1 (RUNX1) and microRNAs have been implicated in drug resistance of TMZ in GBM. In this study, we revealed the underlying mechanism of TMZ resistance and identified miR-128-3p/RUNX1 axis as a novel target for TMZ resistance in GBM. RUNX1 expression was significantly upregulated in GBM tissues as compared to normal tissues, and its expression was even higher in recurrent GBM tissues and TMZ-resistant GBM cells. RUNX1 depletion inhibited the viability, proliferation, migration, invasion and TMZ resistance of GBM cells, which could be rescued by RUNX1 overexpression. We further identified miR-128-3p as a tumor-suppressor whose overexpression restored the sensitivity of TMZ in GBM cells. miR-128-3p negatively regulated RUNX1 and subsequently downregulated multidrug resistance-associated protein 1 (MRP1). Together, the present study indicates that RUNX1 confers TMZ resistance in GBM by upregulating MRP1, which is negatively regulated by miR-128-3p. Targeting miR-128-3p/RUNX1/MRP1 axis provides a potential strategy to overcome TMZ resistance in GBM.